Molekularnogenetska preiskava 300 let starih skeletov iz Auerspergove grobnice - Zupanič-Pajnič, Irena (Zdravniški vestnik, 2013)
Background: In 2009 the archaeologists excavated five skeletons from a 17th-century archaeological site in Ljubljana. They were found in the side chapel of the church in the Franciscans monastery, which was the Auerspergs tomb. Beside the skeletons, the finds revealed a bronze bowl with the heart , and the name of Ferdinand II and the years of birth and death (16551706) engraved. In 2011, we were asked to identify those five skeletons. The skeletons were poorly preserved and bones degraded to small pieces. Fragments of femurs and teeth were preserved only in two skeletons, therefore for the remaining three the fragments of cranium were used for molecular genetic analyses. Methods: We cleaned the bones and teeth, removed surface contamination, and ground them into powder. Prior to DNA isolation, bone or tooth powder was decalcified. DNA was purified in the Biorobot EZ1 device (Qiagen). Nuclear DNA of the samples was quantified using real-time polymerase chain reaction (PCR). Short tandem repeat (STR) typing of autosomal DNA was performed using Investigator ESSplex Kit (Qiagen), the NGM Kit (Applied Biosystems) and the MiniFiler Kit (Applied Biosystems). Typing of the Y-STRs was performed using the YFiler Kit (Applied Biosystems). The two hypervariable regions HVI and HVII of the mtDNA were sequenced. Results: We were able to extract up to 10.7 ng DNA/g of tooth powder from Auersperg chapel archaeological site skeletal remains. We managed to obtain nuclear DNA for successful STR typing from skeletal remains that were over 300 years old. From one skeleton we obtained a complete male genetic profile of autosomal DNA, almost complete Y-STR haplotype, which enabled us to track the paternal line and mtDNA haplotype for HVI and HVII regions, which enabled us to track the maternal line. After comparing the profiles with elimination database, no match was found, and thus the authenticity of genetic profiles was confirmed.Conclusions: Now we are waiting for the family reference samples for comparison with genetic profiles obtained in order to identify the excavated skeletons. This is the first archaeogenetic research performed in Slovenia.
Keywords: ancient DNA; DNA; genetic typing; genetska tipizacija; kosti; molekularnogenetske preiskave; skelet; skeleton; sodna medicina; starodavna DNA; teeth; zobje